2015
DOI: 10.1371/journal.pone.0122401
|View full text |Cite
|
Sign up to set email alerts
|

Bursting Regimes in a Reaction-Diffusion System with Action Potential-Dependent Equilibrium

Abstract: The equilibrium Nernst potential plays a critical role in neural cell dynamics. A common approximation used in studying electrical dynamics of excitable cells is that the ionic concentrations inside and outside the cell membranes act as charge reservoirs and remain effectively constant during excitation events. Research into brain electrical activity suggests that relaxing this assumption may provide a better understanding of normal and pathophysiological functioning of the brain. In this paper we explore time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Conversely, it has been suggested that some biological axons may show properties of crossing action potentials [16], and that Hodgkin-Huxley type models may be inadequate for representing some axons. This view has recently been challenged in a study [47] demonstrating that in the particular case of small neurons, modeled with a reduced Hodgkin-Huxley system (Morris-Lecar equations [48,49]), leading-order effects elicit soliton-like behaviors. In specific, by incorporating a variable Nernst potential into the conventional Morris-Lecar reaction-diffusion model, emergent complex spatiotemporal dynamics of axon excitability, including soliton-like behaviors, were demonstrated [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, it has been suggested that some biological axons may show properties of crossing action potentials [16], and that Hodgkin-Huxley type models may be inadequate for representing some axons. This view has recently been challenged in a study [47] demonstrating that in the particular case of small neurons, modeled with a reduced Hodgkin-Huxley system (Morris-Lecar equations [48,49]), leading-order effects elicit soliton-like behaviors. In specific, by incorporating a variable Nernst potential into the conventional Morris-Lecar reaction-diffusion model, emergent complex spatiotemporal dynamics of axon excitability, including soliton-like behaviors, were demonstrated [47].…”
Section: Discussionmentioning
confidence: 99%
“…This view has recently been challenged in a study [47] demonstrating that in the particular case of small neurons, modeled with a reduced Hodgkin-Huxley system (Morris-Lecar equations [48,49]), leading-order effects elicit soliton-like behaviors. In specific, by incorporating a variable Nernst potential into the conventional Morris-Lecar reaction-diffusion model, emergent complex spatiotemporal dynamics of axon excitability, including soliton-like behaviors, were demonstrated [47]. Thus, soliton-like regimes may be common in excitable membranes, and indeed there is experimental evidence in the form of action potential reflection at axon branch points [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells are coupled by the Ohmic currents through GJs which corresponds to the discretized version of a diffusive coupling (see e.g. [28] for a recent example of complex pattern generation with such a coupling); for recent studies of wave propagation using the alternative spatially extended coupling by an integral kernel, see e.g. [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we extend the above approaches by deriving a cable model that considers the effects of changes to ionic concentration gradients through a conduction process, which leads to changes in equilibrium potentials when ions are in solution and ionic flow is inhomogeneous [ 28 ]. This is the first study in which electrical conduction of polarization-induced capacitive current in a homogenous core-conductor reflects upon ionic concentration gradients without explicitly modeling electrodiffusion of ions (since cable theory ignores the effects of changes in ionic concentrations that lead to changes in Nernst potentials when molecular ions are in bulk solutions).…”
Section: Introductionmentioning
confidence: 99%